2019
DOI: 10.1109/tii.2018.2875529
|View full text |Cite
|
Sign up to set email alerts
|

Detecting False Data Injection Attacks Against Power System State Estimation With Fast Go-Decomposition Approach

Abstract: State estimation is a fundamental function in modern energy management system (EMS), but its results may be vulnerable to false data injection attacks (FDIA). FDIA is able to change the estimation results without being detected by the traditional bad data detection algorithms. In this paper, we propose an accurate and computational attractive approach for FDIA detection. We first rely on the low rank characteristic of the measurement matrix and the sparsity of the attack matrix to reformulate the FDIA detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Based on the decentralized nature of the proposed method, privacy among utilities could be increased and this led to a reduction in the size of the problem, which greatly decreased computational burden. In [19], it was shown that the FDI attack detection problem can be formed as a matrix separation problem due to the nature of the attack matrix, which is a sparse matrix, and the measurement matrix, which is a low-rank matrix. The present matrix separation approaches, such as the Augmented Lagrangian Method (ALM), Low-Rank Matrix Factorization (LRMF), and Double-Noise-Dual-Problem (DNDP)-ALM, suffer from higher computational time and lower accuracy.…”
Section: State Estimation Methodsmentioning
confidence: 99%
“…Based on the decentralized nature of the proposed method, privacy among utilities could be increased and this led to a reduction in the size of the problem, which greatly decreased computational burden. In [19], it was shown that the FDI attack detection problem can be formed as a matrix separation problem due to the nature of the attack matrix, which is a sparse matrix, and the measurement matrix, which is a low-rank matrix. The present matrix separation approaches, such as the Augmented Lagrangian Method (ALM), Low-Rank Matrix Factorization (LRMF), and Double-Noise-Dual-Problem (DNDP)-ALM, suffer from higher computational time and lower accuracy.…”
Section: State Estimation Methodsmentioning
confidence: 99%
“…The authors in [21][22] suggested both accurate and approximate calculations, using the graphical strategies, to choose the basic number estimates besides system protection of many FDI attacks by state factors. For the next sort, the establishment of the power structure is important to the attacker's earlier knowledge.…”
Section: Related Workmentioning
confidence: 99%
“…To detect the attacks, using the Kalman filters, the system states are predicted and using generalized likelihood ratio approach the attack parameters are estimated. Considering low rank matrix of the measurement and sparse Jacobian of the electricity system, three different detection methods of FDI are compared in [13]. In this reference, augmented Lagrangian multipliers (ALM) and low rank matrix factorization method as bench mark algorithms to detect noisy measurements, are compared with Go decomposition method.…”
Section: A Current State Of Artmentioning
confidence: 99%